1999
DOI: 10.1073/pnas.96.22.12465
|View full text |Cite
|
Sign up to set email alerts
|

The solution structure of the Zα domain of the human RNA editing enzyme ADAR1 reveals a prepositioned binding surface for Z-DNA

Abstract: Double-stranded RNA deaminase I (ADAR1) contains the Z-DNA binding domain Z␣. Here we report the solution structure of free Z␣ and map the interaction surface with Z-DNA, confirming roles previously assigned to residues by mutagenesis. Comparison with the crystal structure of the (Z␣) 2͞Z-DNA complex shows that most Z-DNA contacting residues in free Z␣ are prepositioned to bind Z-DNA, thus minimizing the entropic cost of binding. Comparison with homologous (␣؉␤)helix-turn-helix͞B-DNA complexes suggests that bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 25 publications
4
88
0
Order By: Relevance
“…The ADAR gene spans 30 kb and contains 15 exons (Wang et al, 1995). Two Z-alpha domains, three dsRNAbinding domains and the putative deaminase domain are located in exon 2, exons 2-7 and exons 9-15, respectively (Wang et al, 1995;Schade et al, 1999). The heterozygosity for the ADAR knockout causes embryonic lethality in mice (Wang et al, 2000), whereas patients with DSH have a good prognosis of dyschromatosis, which is localized specifically on the backs of hands and on tops of the feet.…”
Section: Discussionmentioning
confidence: 99%
“…The ADAR gene spans 30 kb and contains 15 exons (Wang et al, 1995). Two Z-alpha domains, three dsRNAbinding domains and the putative deaminase domain are located in exon 2, exons 2-7 and exons 9-15, respectively (Wang et al, 1995;Schade et al, 1999). The heterozygosity for the ADAR knockout causes embryonic lethality in mice (Wang et al, 2000), whereas patients with DSH have a good prognosis of dyschromatosis, which is localized specifically on the backs of hands and on tops of the feet.…”
Section: Discussionmentioning
confidence: 99%
“…The side chains of the other residues in this loop (D60, D61, I62, and R65) are flexible in the structural ensemble, giving this loop the shape of a solvent accessible finger with a rigid backbone. Mutational (5) and structural studies (7,9) have demonstrated that this distinctly conserved feature is essential for selective interaction of the homologous Z␣ ADAR1 domain with Z-DNA. In the co-crystal structure of Z␣ ADAR1 and Z-DNA, the protein makes several important van der Waals contacts to Z-DNA.…”
Section: Resultsmentioning
confidence: 99%
“…Alternating d(CG) n oligomers have been successfully used to study the interaction of the Z-DNA-binding domains Z␣ ADAR1 (7,9) and Z␣ DLM1 (8) with Z-DNA. In contrast to these high-affinity Z-DNA-binding homologues, Z␣ E3L does not f lip the B-DNA conformation of these substrates into the Zconformation when incubated with each other under physiological buffer conditions at micromolar concentrations (3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations